PORTRAYING CHILD CHARACTERS IN GENDER PERSPECTIVE: EVALUATION OF PARENTS AWARENESS ABOUT GENDER STEREOTYPES IN TURKISH TELEVISION ADVERTISEMENTS - GUL UNLU, DERYA (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2018)
As individual becomes a part of social life, he/she starts to learn and interiorize gender roles determined by social structure. Like all social structures, this gender distinction can also be found in media content, because media products are both produced by individuals, who have cultural codes, and also reflect the values of the target audience addressed in order to attract attention. When media products are analysed as the reflectors of gender relations, it can be suggested that child roles used in television advertisements are dependent of these relations. Seeing advertisements between or during the programs he/she watches on television, the child perceives boys and girls as symbolic models. Therefore, investigating the awareness of parents about the contents of television advertisements their children watch, and children's tendencies to take the contents in television advertisements as models is considered important. For this reason, the study aims to investigate parents' opinions about taking these roles as models and their awareness about the connection between these roles and gender relations through child roles presented in television advertisements. Face-to-face interviews were conducted with 20 parents of male and female children between the ages of 7-14. As a result of the research, it was determined that parents do not consider child representations in advertisements realistic, they are aware of the gender-based distinctions between child characters in advertisements, and they are of the opinion that television advertisements have short term effects on children.
Keywords: gender; parent; child; advertising; TELEVISION